Characterization of patients treated by rehabilitation service after establishing of an acute stroke unit in a Brazilian hospital - Luvizutto, Gustavo Jose [UNESP]; Orsi Gameiro, Monica de Oliveira [UNESP]; Schelp, Arthur Oscar [UNESP]; Braga, Gabriel Pereira [UNESP]; Ribeiro, Priscila Watson [UNESP]; Bazan, Rodrigo [UNESP] (Soc Physical Therapy Science, 2015)
[Purpose] The study aimed to characterize patients treated by rehabilitation section after establishment of an acute stroke unit. [Subjects and Methods] Medical consultation records of individuals with ischemic stroke were studied retrospectively, excluding individuals with hemorrhagic stroke, thrombolysis, previous Modified Rankin Scale >= 1, prior stroke, structural bone deformities, associated neurological disease, and prior cognitive deficit. The data evaluated were age, gender, etiology, localization, treatment received, ictus onset, hospitalization time, discharge date, and date of first evaluation at the rehabilitation center. The Modified Rankin Scale in 90 days after ictus was utilized to measure functional incapacity with the individuals divided into two groups, before and after acute stroke unit implementation (2010). Functional incapacity was compared between before and after acute stroke unit implementation by the Mann-Whitney test, chi(2) test and Fisher's exact test. [Results] The medical records of 170 patients were evaluated. In the group evaluated after 2010, the patients were significantly older and presented a shorter time between hospitalization and discharge, shorter time until the first evaluation in rehabilitation, and increased percentage of mild incapacity (Modified Rankin Scale = 0 to 2). [Conclusion] After acute stroke unit implementation, the patients treated in the rehabilitation section presented a shorter hospitalization time and rehabilitation delay and less functional incapacity.
Keywords: Stroke; Acute stroke unit; Rehabilitation outcome